2018
DOI: 10.3847/1538-4357/aacc25
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-red Galaxies Signpost Candidate Protoclusters at High Redshift

Abstract: (2018) 'Ultra-red galaxies signpost candidate protoclusters at high redshift.', Astrophysical journal., 862 (2). p. 96.Further information on publisher's website:https://doi.org/10.3847/1538-4357/aacc25Publisher's copyright statement: c 2018. The American Astronomical Society. All rights reserved. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 122 publications
(205 reference statements)
4
41
0
Order By: Relevance
“…Of the 6 LABOCA sources reported by Lewis et al within 3 arcmin of the 10 central, confirmed members of the DRC, our ALMA imaging spectroscopy confirms 4 new members of the protocluster at z = 4 (2 towards a single LABOCA source), while 2 are shown via robust line detections to lie at other, unknown redshifts along the line of sight, and 1 is shown to be a blank sub-mm field. This rate of associations is in line with the ∼2.15× overdensity predicted by Lewis et al (2018), whose individual photometric redshift estimates are shown to have been useful.…”
Section: S U M M a Ry A N D C O N C L U D I N G R E M A R K Ssupporting
confidence: 85%
See 3 more Smart Citations
“…Of the 6 LABOCA sources reported by Lewis et al within 3 arcmin of the 10 central, confirmed members of the DRC, our ALMA imaging spectroscopy confirms 4 new members of the protocluster at z = 4 (2 towards a single LABOCA source), while 2 are shown via robust line detections to lie at other, unknown redshifts along the line of sight, and 1 is shown to be a blank sub-mm field. This rate of associations is in line with the ∼2.15× overdensity predicted by Lewis et al (2018), whose individual photometric redshift estimates are shown to have been useful.…”
Section: S U M M a Ry A N D C O N C L U D I N G R E M A R K Ssupporting
confidence: 85%
“…The field of LABOCA source H was found to be devoid of continuum emission and it is therefore likely that the LABOCA detection was spurious, as already hinted by the empty Herschel SPIRE maps reported by Lewis et al (2018). ALMA 97-GHz line-free continuum emission with zeroth-moment spectral-line emission overlaid as contours in green (blue for D) for LABOCA sources C-H.…”
Section: R E S U Lt Smentioning
confidence: 80%
See 2 more Smart Citations
“…clusters that are still in the process of forming), allowing for more robust determination of whether there is a reversal at high redshift (e.g. Andreon et al 2014, Clements et al 2014, Bleem et al 2015, Alexander et al 2016, Franck & McGaugh 2016, Cai et al 2017, Daddi et al 2017, Mantz et al 2017, Umehata et al 2017, Casasola et al 2018, Lewis et al 2018, Oteo et al 2018, Zeballos et al 2018 CL J1449+0856 (hereafter CLJ1449, RA= 222.3083 Dec=8.9392) is one of the highest redshift, fully virialized, mature X-ray emitting clusters known. The cluster was first identified as an over-density of red galaxies during Spitzer observations of the so called 'Daddi fields' (Daddi et al 2000).…”
Section: Introductionmentioning
confidence: 99%